Prevalence of sexually transmitted infections and associated factors among male prisoners in Great Tehran Prison by active case finding - Behnam Farhoudi; Elnaz Shahmohamadi; Seyedahmad Seyedalinaghi; SeyedAlireza Nadji; Fatemeh Pahlaviani; Mehrzad Tashakorian (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Sexually transmitted infections (STIs) are transferred from one person to another through sexual contact. Despite high rates of STIs in prisons, there is no sufficient screening, prevention, and treatment programs to prevent STIs transmission among prisoners. Due to the contact between prisoners and general population during visiting or after release, controlling STIs transmission among prisoners helps significantly decrease the rate of STIs in society. Therefore, recognizing and reducing risky behaviors among prisoners may have remarkable effects in this regard. This study was performed to evaluate the prevalence and risk factors of STIs among incarcerated men through clinical examination and molecular tests, and to recommend possible and proper solutions for controlling STIs in prisons.